Critical Velocity and Backlayering Conditions in Rail Tunnel Fires: State-of-the-Art Review. (28th May 2019) - Haddad, Razieh Khaksari; Maluk, Cristian; Reda, Eslam; Harun, Zambri
Abstract : The use of interurban and urban trains has become the preferred choice for millions of daily commuters around the world. Despite the huge public investment for train technology and mayor rail infrastructure (e.g., tunnels), train safety is still a subject of concern. The work described herein reviews the state of the art on research related to critical velocity and backlayering conditions in tunnel fires. The review on backlayering conditions includes the effect of blockages, inclination, and the location of the fire source. The review herein focuses on experimental and theoretical research, although it excludes research studies using numerical modeling. Many studies have used scaled tunnel structures for experimental testing; nevertheless, there are various scaling challenges associated with these studies. For example, very little work has been done on flame length, fire source location, and the effect of more than one blockage, and how results on scaled experiments represent the behaviour at real-scale. The review sheds light on the current hazards associated with fires in rail tunnels.